The Effectivness of Using Dictionaries on EFL Students’ Vocabulary Memorization The Case of Second Year EFL Students at Mohamed Boudiaf University of M’Sila - HADIBI Bakhta, Dr. Guermi Nour El-houda (université mohamed boudiaf .m'sila, 2023)
ABSTRACT This dissertation investigates the effectiveness of using dictionaries for vocabulary memorization among (EFL) students. Dictionaries are considered vital tools in language learning, providing learners with valuable information about words and their meanings. However, the extent of their effectiveness in vocabulary acquisition is a subject of ongoing debate. This study aims to address this research gap by examining the impact of dictionary use on EFL students' vocabulary learning.The study adopts an exploratory and partially descriptive research methodology. A questionnaire was administered to gather data from 25 EFL students and 13 teachers at Msila University. The research focuses on various aspects, including the benefits and challenges of using dictionaries, different strategies for effective dictionary use, and the role of dictionary-based instruction in enhancing vocabulary acquisition. The study confirms the research assumptions and the positive impact of active and comprehensive dictionary use on vocabulary learning. Common challenges faced by learners include selecting appropriate dictionaries, interpreting word definitions, and integrating new vocabulary. Active dictionary strategies, such as analyzing example sentences and utilizing pronunciation guides, are emphasized for effective vocabulary learning. The research provides insights into students' and teachers' perceptions and practices, highlighting the importance of tailored instruction, digital resource integration, and effective dictionary use strategies. This research enhances understanding of the role of dictionaries in vocabulary learning and offers practical recommendations for enhancing vocabulary memorization among EFL learners.
Keywords: Key words: EFL / Vocabulary / Dictionary